Integrating service user and practitioner expertise within a web-based system for collaborative mental-health risk and safety management. Issue 10 (October 2015) - Buckingham, Christopher D.; Adams, Ann; Vail, Laura; Kumar, Ashish; Ahmed, Abu; Whelan, Annie; Karasouli, Eleni
Highlights Clinicians and patients can share expertise within a single cognitive model. The GRiST online cognitive model helps patients talk about mental health. Patients prefer to focus on positive aspects of their mental health. Patients like to explore risk issues but need structured access and feedback. Patients can self-manage mental health with web-based decision support.